1995
DOI: 10.1123/japa.3.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Aging, and Psychological Well-Being

Abstract: This review examines the effects of exercise and physical activity on the psychological well-being of older adults. Unlike most of the literature in this area, this review focuses primarily on those psychosocial outcomes that are generally positive in nature. As well as considering the overall effects of physical activity, the roles of program length, subject sex, age, physical fitness, and measurement are considered. Overall, the results of the 38 studies reviewed are overwhelmingly positive, with the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
2
25

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 54 publications
6
142
2
25
Order By: Relevance
“…Review articles concentrated mostly on affective ( 1 Reviews of studies with the aged a Reviews of studies with the aged concept of well-being. Other authors, in contrast, concentrated on positive aspects of well-being [8] or even exclusively on positive affect [17,18]. (c) Whereas some authors limited themselves exclusively to single or only a few demarcated areas of SWB (e.g., [17,18,42,45,46]), others covered all or the majority of categories addressed here (e.g., [7,9,47]).…”
Section: Use Of Swb In Exercise-related Secondary Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Review articles concentrated mostly on affective ( 1 Reviews of studies with the aged a Reviews of studies with the aged concept of well-being. Other authors, in contrast, concentrated on positive aspects of well-being [8] or even exclusively on positive affect [17,18]. (c) Whereas some authors limited themselves exclusively to single or only a few demarcated areas of SWB (e.g., [17,18,42,45,46]), others covered all or the majority of categories addressed here (e.g., [7,9,47]).…”
Section: Use Of Swb In Exercise-related Secondary Analysesmentioning
confidence: 99%
“…Hence, either features of exercise variables, environmental variables, or particular characteristics of participants are identified that have a more or less confirmed effect on SWB. For example, it is assumed that exercise can bring about a stronger gain in self-efficacy with increasing age [66].…”
Section: Statistical Moderation Versus Theoretical and Content-relatementioning
confidence: 99%
See 2 more Smart Citations
“…In most studies, the frequency of exercise varied from 2 to 5 days per week (M=3.54) and 54 min, sessions (McAuley & Rudolf, 1995). However the benefit of lower frequency training regiments has not been adequately addressed (Valliant & Asu, 1985) and, therefore, the minimum stimulus required to facilitate improvement of functional status is not well established in older populations.…”
Section: Introductionmentioning
confidence: 99%